IMPLEMENTASI LKPD BERINTEGRASI DENGAN QR CODE TERHADAP PEMAHAMAN KONSEP DAN MOTIVASI BELAJAR PADA MATERI EKOSISTEM - Grecia Imestiara Agatha; Rivanna Citraning Rachmawati; Maria Ulfah; Raden Edy Priyatna (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Research on the Implementation of LKPD integrated with the Qr Code on Concept Understanding and Learning Motivation in Ecosystem Materials. The purpose of this study was to find out the understanding of concepts and student motivation through LKPD Qr code Solutions by implementing QR-Code assisted LKPD learning. Sampling used the random sampling technique, which where the sample is chosen randomly or freely according to the wishes of the researcher. The worksheets are adapted to the Problem Based Learning learning model and the data is taken from the results of students' answers. Based on the results of the study of students' understanding of concepts and learning motivation through the LKPD Qr code of class X.8 students of SMA N 10 Semarang, the average percentage of understanding of concepts through daily tests was 84.68% which was classified as high and learning motivation was also included in high category because the teacher still uses teacher center learning with new innovations by making Qr code LKPD makes students enthusiastic in learning and has high learning motivation therefore the understanding of the concept given by the teacher can be well received